The night child : a novel - Quinn, Anna (Blackstone Publishing, 2018)
Nora Brown teaches high school English and lives a quiet life in Seattle with her husband and six-year-old daughter. But one November day, moments after dismissing her class, a girl's face appears above the students' desks and terror rushes through Nora's body. Twenty-four hours later, while on Thanksgiving vacation, the face appears again. Shaken and unsteady, Nora meets with neurologists and eventually, a psychiatrist. As the story progresses, a terrible secret is discovered--a secret that pushes Nora toward an even deeper psychological breakdown.